HUBUNGAN SLEEP HYGIENE DENGAN KUALITAS TIDUR PADA LANSIA DI DUSUN VI SILO BONTO KECAMATAN SILAU LAUT TAHUN 2022 - Rentawati Purba; Dewi Tiansa Barus (Jurnal Penelitian Keperawatan Medik, 2023)
Cell deterioration occurs in old age due to the aging mechanism, which can result in physical decline, weakened organs, and various regenerative problems. The most common problem that occurs in the elderly due to the aging process is a change in sleep quality. Insomnia is a common sleep quality disorder in the elderly that results in decreased sleep quality. Good sleep hygiene can help improve sleep quality. The purpose of this study is to determine the relationship between sleep hygiene and sleep quality in the elderly in Dusun VI Silo Bonto, Silau Laut District. This quantitative study used a correlation method with a cross-sectional design approach. The sampling technique used was total sampling with a sample size of 46 respondents. The data analysis used was the Chi-Square test. The results of the Chi-Square test were obtained with a significance level of a = 0.05. If the value is â‰¤ 0.05 (a: 5%), then the hypothesis is accepted. The statistical test result obtained a value of 0.020, which is smaller than the alpha (a) value of 0.05, thus it can be concluded that there is a significant relationship between sleep hygiene and sleep quality in the elderly in Dusun VI Silo Bonto, Silau Laut District in 2022, so Ha is accepted and Ho is rejected.